1999
DOI: 10.1046/j.1460-9568.1999.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Q/R editing of the rat GluR5 and GluR6 kainate receptors in vivo and in vitro: evidence for independent developmental, pathological and cellular regulation

Abstract: Kainate (KA) is a potent neuroexcitatory agent in several areas of the adult brain, with convulsant and excitotoxic properties that increase as ontogeny proceeds. Besides its depolarizing actions, KA may enhance intracellular accumulation of Ca2+ to promote selective neuronal damage. The effects of KA are mediated by specific receptors recently considered to be involved in fast neurotransmission and that can be activated synaptically. KA receptors, e.g. GluR5 and GluR6 have been characterized by molecular clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 92 publications
2
89
1
2
Order By: Relevance
“…Among the high grade tumors, four out of six showed a mild decrease in editing activity at this site ( Table 1). The RNA editing of the GluR-B transcript at the Arg/Gly site and of the GluR-6 transcript at the Ile/Val, Tyr/Cys, and Gln/ Arg sites varied among different regions of the brain, as expected from observations in mice (24). The percentage of editing at all the sites analyzed was lower in astrocytomas when compared with the corresponding normal control tissue.…”
Section: Resultssupporting
confidence: 59%
“…Among the high grade tumors, four out of six showed a mild decrease in editing activity at this site ( Table 1). The RNA editing of the GluR-B transcript at the Arg/Gly site and of the GluR-6 transcript at the Ile/Val, Tyr/Cys, and Gln/ Arg sites varied among different regions of the brain, as expected from observations in mice (24). The percentage of editing at all the sites analyzed was lower in astrocytomas when compared with the corresponding normal control tissue.…”
Section: Resultssupporting
confidence: 59%
“…AMPA receptors assemble as dimer of dimers, and this process is regulated by the amino acid residing at the Q/R site in GluR2 subunits (18,24). It is not clear if kainate receptors, which exhibit much greater variability than GluR2 in the degree of their Q/R site RNA editing in situ (39,40), are subject to the same rules of oligomerization, but domain-swapping experiments suggested that this might be the case (41). Our co-immunoprecipitations of GFP-GluR6 with mutant KA2 subunits suggest that, despite retention, at least one subunit of KA2 can assemble with a GluR6 subunit in the ER, although we do not know if tetrameric receptors are formed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that both the unusual properties of GABA A receptors and the expression of ''silent'' GluR5 receptors are unlikely to be related to altered posttranslational processes or to receptor modulation by host membrane proteins and lipids. Interestingly, changes in receptor editing during seizures may be a reason for altered receptor activity (32).…”
Section: Discussionmentioning
confidence: 99%